2012
DOI: 10.1080/00380768.2012.703610
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and assemblage of major capsid genes (g23) of T4-type bacteriophages in paddy field soils during rice growth season in Northeast China

Abstract: Although bacteriophages (phages) are ubiquitous and the most abundant biological entities on Earth, the genetic information on their diversity and community composition in natural environments, particularly in soils, is limited. This study elucidated the diversity and composition of T4-type phages by analyzing partial major capsid gene (g23) sequences in DNA extracts from five paddy field soils in Northeast China during the flooded period of rice (Oryza sativa L.) cultivation. In total, 106 different g23 clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Even in the similar environment of paddy field, the distribution of g23 genes was also distinctly different between Japan and NE China, and several specific groups of T4-type phages were observed in the two countries [36]. Thus, we concluded that the T4-type phage communities in terrestrial environments are determined by both biogeographic and ecological processes [35].…”
Section: Discussionmentioning
confidence: 83%
“…Even in the similar environment of paddy field, the distribution of g23 genes was also distinctly different between Japan and NE China, and several specific groups of T4-type phages were observed in the two countries [36]. Thus, we concluded that the T4-type phage communities in terrestrial environments are determined by both biogeographic and ecological processes [35].…”
Section: Discussionmentioning
confidence: 83%
“…They revealed that g23 homologues of the T4 are ubiquitous in aquatic environments. Using this primer set, a few studies then investigated the diversity of T4‐like myoviruses in both marine and freshwater ecosystems (Filée et al ., ; López‐Bueno et al ., ; Butina et al ., , ; Huang et al ., ; Jamindar et al ., ; Parvathi, Zhong & Jacquet, ; Bellas & Anesio, ; Zheng et al ., ), but also in soil and sediments (Jia et al ., ; Fujii et al ., ; Wang et al ., ,b, ; Fujihara et al ., ; Liu et al ., , ; Li et al ., ; Bellas & Anesio, ). These studies showed that T4‐like myoviruses are prevalent viral components in nature and exhibit distinct diversity between geographical locations or environments.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature addresses the microbial ecology of paddy fields, including total bacterial and fungal communities3, methanogenic archaea4, methanotrophic bacteria5, and ammonia-oxidizing bacteria and archaea6. Recently, research on viral ecology or phage ecology in paddy ecosystems has aroused much attention789101112131415. For instance, Nakayama et al 9.…”
mentioning
confidence: 99%